Just grandpa and me - Mayer, Mercer 1943- (New York Golden Books, 1985)
A little creature and his grandfather have fun on a trip to the department store.
"A Paperwing Press book."
Keywords: Grandfathers -- Fiction; Department stores -- Fiction